Green Nanotechnology Sintesis Nanopartikel (NP) dari Tanaman untuk Bioremediasi Logam Berat Hg, Cr, dan Pb Kajian Literatur - Hasna Labib Lathifah; Adilla Syahsiyatun Najah; Marsya Naranissa Puteri Santoso (Jurnal Biodiversitas dan Bioteknologi, 2025)
Heavy metals are toxic pollutants that cause environmental pollution. Heavy metals that enter the environment cannot be degraded either biologically or chemically and can remain in the environment for a long time. Bioremediation is a technique to protect the environment from contaminants using biological agents. One of the Green Nanotechnology technologies can contribute to bioremediation. Therefore, the purpose of this literature review is to find out the concept of green nanotechnology bioremediation by synthesizing nanoparticles from plants for bioremediation of heavy waste hg, cr, Pb. the literature review method used is an online-based literature review with sources derived from Google Scholar, Pubmed and Sciencedirect. Plant extracts were obtained in both aqueous and non-aqueous media using hot solvents or cold extraction methods. The plant extracts were then filtered and a solution suitable for the nanoparticles to be synthesized was added. Nanotechnology bioremediation has high potential to be used in surface water, groundwater, and wastewater treatment technologies to filter on a nanoscale so that water is able to pass but large materials such as bacteria and viruses and their products (toxins) will be filtered out on nanoparticles. In addition, catalysts and filters can be designed to produce high adsorption strength so that they can absorb heavy metal ions.